Collaborating to Offer Small Courses/Subjects Forum : The University of New England, 17-18 May 2007 : Final Report. - Tynan, Belinda (ed); Dunne, Kerry (ed); Smyth, Robyn (ed) (Carrick Institute for Learning and Teaching in Higher Education, 2007)
Final report on the Collaborating to Offer Small Courses/Subjects Forum hosted by the University of New England for the Carrick Institute over two days in May 2007. Includes brief biographies and papers presented at the forum. The papers range across a number of discipline areas and include collaborations that have been tried, those that are well established, and those being developed. The purpose of the forum was to provide an opportunity to share and examine models of collaboration for small courses; the issues that need to be resolved in successful collaborations to support small subjects; and courses/disciplines/other instances where collaborations are being explored.